Leaving the chasm behind: Autoethnography, creativity and the search for identity in academia - Atherton, Pete Frederick (PRISM: Casting New Light on Learning, Theory and Practice, 2022)
This paper examines visual narratology as a way of presenting qualitative primary data. The paper is an autoethnographic study with the overall goal of helping educators understand their digital literacies in a time of uncertainty and flux. The researcher deployed thematic analysis as the organising methodological framework. This performative autoethnographic method provided creative freedom and the satisfaction of a renewed perspective for the author (Jay and Johnson 2002). This primary qualitative data was given legitimacy and structure by the use of thematic analysis as a methodology. The findings support Bochner’s (1994) idea that social science research can benefit from deliberately value-laden stories alongside empirical data and theories. The findings also developed the author’s previous autoethnographic paper, which drew on his own social media posts as qualitative and quantitative data Atherton (2020b).